Customer Service Satisfaction Dan Trust Sebagai Brand Loyality Pada Produk Kosmetik G2G - Ziadatul Khairini; Didin Hadi Saputra (CV. Dalle’ Deceng Abeeayla, 2026)
This study aims to analyze the quality of customer service and the level of consumer trust in G2G cosmetic products. This study used quantitative methods, collecting data through questionnaires distributed to 103 respondents who are users of G2G cosmetic products. The data obtained were analyzed descriptively to determine respondents' perceptions of the variables of service satisfaction, consumer trust, service responsiveness, service reliability, and service empathy. The results showed that, in general, the quality of customer service for G2G cosmetic products was in the good category. The consumer trust variable received the highest rating, indicating that the majority of respondents believed in the safety of G2G cosmetic products. Furthermore, customer satisfaction, responsiveness, reliability, and service empathy were also rated positively, although some respondents still gave moderate to low ratings, indicating service inconsistencies. The conclusion of this study is that G2G customer service has been able to provide good service and build consumer trust. However, continuous improvement of service quality is still needed, particularly in the aspects of empathy and response consistency. Therefore, it is recommended that the company increase customer service training and performance evaluation to improve customer satisfaction and loyalty. The implications of this research are expected to be a consideration for G2G management in formulating strategies to improve service quality and strengthen long-term relationships with consumers.